Comparison of Computerized Patients versus Live Moulaged Actors for a Mass-casualty Drill. Issue 5 (12th August 2015) - Claudius, Ilene; Kaji, Amy; Santillanes, Genevieve; Cicero, Mark; Donofrio, J. Joelle; Gausche-Hill, Marianne; Srinivasan, Saranya; Chang, Todd P.
Abstract: Introduction: Multiple modalities for simulating mass-casualty scenarios exist; however, the ideal modality for education and drilling of mass-casualty incident (MCI) triage is not established. Hypothesis/Problem: Medical student triage accuracy and time to triage for computer-based simulated victims and live moulaged actors using the pediatric version of the Simple Triage and Rapid Treatment (JumpSTART) mass-casualty triage tool were compared, anticipating that student performance and experience would be equivalent. Methods: The victim scenarios were created from actual trauma records from pediatric high-mechanism trauma presenting to a participating Level 1 trauma center. The student-reported fidelity of the two modalities was also measured. Comparisons were done using nonparametric statistics and regression analysis using generalized estimating equations. Results: Thirty-three students triaged four live patients and seven computerized patients representing a spectrum of minor, immediate, delayed, and expectant victims. Of the live simulated patients, 92.4% were given accurate triage designations versus 81.8% for the computerized scenarios ( P =.005). The median time to triage of live actors was 57 seconds (IQR=45-66) versus 80 seconds (IQR=58-106) for the computerized patients ( P <.0001). The moulaged actors were felt to offer a more realistic encounter by 88% of the participants, with a higher associated stress level. Conclusion: While potentially easier and more convenient to accomplish, computerized scenarios offered less fidelity than live moulaged actors for the purposes of MCI drilling. Medical students triaged live actors more accurately and more quickly than victims shown in a computerized simulation. I Claudius, A Kaji, G Santillanes, M Cicero, JJ Donofrio, M Gausche-Hill, S Srinivasan, TP Chang .Comparison of computerized patients versus live moulaged actors for a mass-casualty drill .Prehosp Disaster Med. 2015 ;30 (5 ):438 –442 .